Priene, Türkei: Denkmalpflege und Konservierung in einer "Musterstadt" - Filges, Axel (e-Forschungsberichte des DAI, 2023)
In 2012 a completely new concept for the preservation and presentation of the ancient city was created. The focus of the DAI-financed works in Priene during the years 2012–2014 was the documentation and restoration of structural damages of buildings. Main areas of work were the restoration of the Roman bath building, the new surrounding of a test trench of the old excavation, the reconstruction of a high wall corner in the area of the food market, the removal of a broken wall just beside the main route for visitors, and the consolidation of the walls of residential buildings in the western part of the city.